Berberine hydrochloride-loaded liposomes-in-hydrogel microneedles achieve the efficient treatment for psoriasis - Si Shen; Wang Shen; Lu Wang; Bin Sun; Yongli Zhang; Yong Zhang; Ruoyang Jia; Yang Wu; Xue Chen; Keang Cao; Yuqing Fang; Hongmei Xia (Materials Today Bio)
Psoriasis is a common immune-mediated squamous skin disease, primarily characterized by the over proliferation of keratinocytes and a significant thickening of the stratum corneum. Traditional systemic drug delivery therapies often fall short due to low drug bioavailability and significant toxic side effects. Topical medications, while capable of achieving local or systemic treatment via transdermal routes, face limitations in psoriasis patients due to the abnormal thickening of the epidermis, which reduces skin permeability and hampers drug penetration efficiency. Hydrogel microneedles, as an emerging transdermal drug delivery technology, offer significant advantages such as high permeability, ease of use, low toxicity and side effects, and controlled release. Therefore, this study developed a liposome-hydrogel microneedle delivery system for the administration of berberine hydrochloride. We successfully prepared berberine hydrochloride-loaded liposomes (Ber-LPs) with high encapsulation efficiency and good stability, and integrated them into hydrogel microneedles crosslinked with PVA and PEGDA (Ber-LPs-PEGDA&PVA MNs) through a photocuring method. These microneedles exhibit an intact structure, high mechanical strength, and effective skin penetration. In vivo studies on anti-psoriatic effects showed that, compared to the model group, Ber-LPs-PEGDA&PVA MNs significantly alleviated imiquimod-induced psoriasis-like symptoms in mice, reduced skin epidermal thickness, decreased the expression levels of inflammatory cytokines, and lowered the expression of CD31 and VEGF, demonstrating excellent therapeutic efficacy. Additionally, the microneedles exhibited good drug release properties, antioxidant capacity, and biocompatibility. The novel hydrogel microneedle drug delivery system developed in this study offers a safe and effective solution for the treatment of psoriasis, with significant potential for clinical application.